Endemic Species - Cano Carmona, Eusebio; Maria Musarella, Carmelo; Cano Ortiz, Ana (IntechOpen, 2019)
This book consists of several thematic groups, including botany, zoology and topics related to human health. In regards to botany, chapters discuss endemic plants of Bolivia, Mexico, Italy and the Caribbean. They show the diversity, distribution and conservation of many species. In regards to zoology, the book highlights endemic primates and reptiles. Additionally, the book presents other environmental issues relevant to conservation. This volume also presents topics related to health, some of which are relevant for their implications on health and the economy, is the case of the presence of toxins in the Pacific plankton.All chapters present relevant content for future research or because they are fundamental for territorial management.